Manajemen Pengembangan Madrasah yang Unggul dan Kompetitif - Najib Habibi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2020)
An abstract should accompany each manuscript; it should be completely self-consistent (i.e., with no figure, table, equation or reference citations), not exceeding 250 words and written as a single paragraph. Abstract should include aims of the research, methodology and findings. As one of the deep-rooted educational institutions in the community, the madrasa is a manifestation of the Indonesian nation's culture that must be cared for and developed. Because it cannot be denied that this institution has contributed greatly, namely to educate millions of young cadres of this nation without strings attached. Therefore, it is very improper if madrassas are marginalized and accused as the culprits of the nation's decline, and we should be able to prove with good management, we can develop madrassas and make competitive superior madrasas dare to compete with other public schools. Keywords: Management, Development, An Exellent Islamic School.